Therapy for digital ulcers in patients with systemic scleroderma - M. N. Starovoitova; O. V. Desinova (Научно-практическая ревматология, 2019)
As of now, there are several pharmacological directions in the treatment and prevention of Raynaud’s syndrome and digital ulcers, including various vasoactive drugs (calcium channel blockers, intravenous prostanoids, endothelin receptor antagonists, phosphodiesterase 5 inhibitors, antiplatelets, and statins). The approach to treating systemic sclerosis-related digital ulcers is multifactorial: prevention of risk factors, local and systemic drug treatment, and surgical treatment if necessary.